Pelatihan Budidaya Hidroponik Sayur Daun: Pemberdayaan Masyarakat Panyirapan Banten, Indonesia di Masa Pandemi Covid-19 - Irva Faozi Anwar; Lia Junita Harahap (Program Studi Pengembangan Masyarakat Islam, 2021)
Abstract:Panyirapan is a village whose community work is dominated by farmers. People are still farming conventionally and do not know the techniques of farming with a hydroponic system. The hydroponic training conducted by BLK Lembang aims to educate the people of Panyirapan village to switch to hydroponic farming that is more environmentally friendly. The training was held from 27 October to 12 November 2020. The training method consisted of providing theory and practice by BLK representative instructors. The theory given to the training participants is an introduction to hydroponics in general, Applying Safety, Occupational Health and Environmental Provisions in the Workplace, as well as the given practice, namely the practice of installing wick systems, NFT, seedlings, making AB Mix stock solutions, transplanting, and standards. operational (SOP) hydroponic gardening. The training participants were 16 people who were heterogeneously selected and grouped into 4 groups. The vegetable crops grown are pakcoy, red lettuce, green lettuce, spinach and kale. The results of the training show that the training participants have competence in the field of hydroponics which is attached to the graduation certificate which is distributed to the trainees at the end of the series of training activities. The training activities provide knowledge to the community, especially the training participants on how to grow modern crops (hydroponics), being able to motivate themselves to become entrepreneurs in the field of hydroponic agriculture by forming a hydroponic farmer group, namely the fragrant blooming hydroponic vegetable community. The community actively sells their harvests in the form of pakcoy, spinach, lettuce and kale to the panyirapan community. Keywords: Hydroponic Training, Community Empowerment, NFT System, Wick System Abstrak:Panyirapan merupakan desa yang pekerjaan masyarakatnya didominasi oleh petani. Masyarakat masih bertani secara konvensional dan kurang mengetahui teknik bercocok tanam dengan sistem hidroponik. Pelatihan hidroponik yang dilakukan oleh BLK Lembang bertujuan untuk mengedukasi masyarakat desa Panyirapan agar beralih ke pertanian hidroponik yang lebih ramah lingkungan. Pelatihan dilaksanakan pada 27 Oktober 2020 hingga 12 November 2020. Metode pelatihan terdiri dari pemberian teori dan praktik oleh instruktur perwakilan BLK. Teori yang diberikan terhadap peserta pelatihan yaitu pengenalan hidroponik secara umum, Menerapkan Ketentuan Keselamatan, Kesehatan Kerja dan Lingkungan di Tempat Kerja, serta praktik yang diberikan yaitu praktik membuat instalasi sistem wick, NFT, semai, membuat larutan stock AB Mix, pindah tanam, dan standar oprasional (SOP) berkebun hidroponik. Peserta pelatihan sebanyak 16 orang yang dipilih secara heterogen dan dikelompokan menjadi 4 kelompok. Komoditas tanaman sayuran yang ditanam yaitu pakcoy, selada merah, selada hijau, bayam dan kangkung. Hasil pelatihan menunjukkan bahwa para peserta pelatihan telah memiliki kompetensi di bidang hidroponik yang terlampir pada sertifikat lulus yang dibagikan kepada para peserta pelatihan di akhir rangkaian kegiatan pelatihan. Kegiatan pelatihan memberikan pengetahuan kepada masyarakat khususnya para peserta pelatihan mengenai cara bercocok tanam modern (hidroponik), mampu motivasi untuk berwirausaha di bidang pertanian hidroponik dengan terbentuknya kelompok tani hidroponik yaitu komunitas sayuran hidroponik mekar wangi. Komunitas tersebut aktif menjual hasil panennya berupa pakcoy, bayam, selada dan kangkung ke lingkungan masyarakat panyirapan. Kata Kunci: Pelatihan Hidroponik, Pemberdayaan Masyarakat, Sistem NFT, Sistem Wick